(untitled) (Universal International Scientific Journal, 2026)
This article examines the role of innovation in higher education and its significance for economic development. Particular attention is paid to the integration of education, science, and industry as a key factor in innovative development. The paper analyzes the improvement of research activities, the effective use of intellectual resources, and the training of highly qualified personnel. It also examines the priority areas of an innovative development strategy and the role of higher education institutions in advancing scientific and innovative activity. It concludes that strengthening the interaction between education, science, and industry is essential for sustainable economic growth.